Considerações sobre a produção de alimentos por árvores e florestas - Arkcoll, D. B. (Acta Amazonica, 1982)
Trees and forest contribute little to most diets. This is surprising as some species seem capable of producing much more food per area than the many annual crops that supply the bulk of our food. It is suggested that this yield potential coupled with agricultural e ecological advantages should lead to research into Increasing food production from all forms of forests and the design of "food forests".